PERAN PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK DISIPLIN PESERTA DIDIK SMP MENURUT TEORI THOMAS LICKONA - Muhadi Muhadi; Ni Nyoman Fransiska; Oktavianus Lede Nono (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2026)
Christian Religious Education (PAK) plays a crucial role in shaping students’ character, particularly amid the increasingly complex digital age. This urgency arises due to the weakening of Christian character practices, reflected in various negative phenomena, such as bullying, violence among students, the fading of good manners, declining social awareness, the destructive misuse of digital media, and increasing intolerance within the school environment. This study aims to analyze the role of Christian Character Education (CCE) in shaping the character of junior high school (SMP) students using a qualitative approach through a literature review, grounded in Thomas Lickona’s character theory. The results indicate that CCE plays a significant role in shaping students’ character through three primary pathways: Bible-based instruction, the cultivation of positive attitudes in daily life, and teachers serving as moral role models. These three pathways align with the three moral dimensions proposed by Lickona, namely moral knowing, moral feeling, and moral behavior. However, there are a number of challenges that hinder the effectiveness of PAK, including a lack of role modeling within the family environment, the overwhelming influence of modern culture, and the negative impact of digital media. Therefore, strong collaboration between schools, families, and churches is needed, along with improvements in the competencies of religious education teachers, so that character education can be implemented effectively and sustainably.